"Feed and Swaddle" method of Infants Undergoing Head CT for minor head injury in the pediatric emergency department – A comparative case review. Issue 154 (September 2022) - Heiman, Eyal; Hessing, Evelyn; Berliner, Elihay; Cytter-Kuint, Ruth; Barak-Corren, Yuval; Weiser, Giora
Highlights: Completion of head imaging in pediatric head injuries requires a timely study and cooperative child. The use of sedation can be limited due to the injury mechanism and the child's young age. A feed and swaddle method helps children fall asleep for the completion of the brain CT. This method can be used safely and successfully in children with mild head injuries even with abnormal findings. Abstract: Introduction: Brain imaging for suspected significant head injuries in pediatric emergency departments is an important and time-sensitive procedure. The use of sedation to successfully complete imaging can be limited due to young age and other injury related factors. Using a non-pharmacological method using feeding and swaddling can be used. This may obviate the need for sedation but can be time consuming. Methods: A retrospective study of all children undergoing brain imaging for head injury during the years 2016–2021. Use of sedation, time to completion and imaging findings were compared. Results: Of 281 children requiring brain imaging, 268 (95.4%) were completed using the feed and swaddle method. Time to imaging completion was similar between sedation and feed and swaddle groups (85.5 min vs. 86 min). Abnormal findings on imaging were found in 186 (69.4%) in the feed and swaddle group and in 10 (77%) of the sedation group. No adverse events were seen in the sedation group. Conclusion: Using the feed and swaddle method can help lower the need for sedation in the under 1 year age group with a successful and timely completion of brain imaging.